การเปลี่ยนแปลงอัตราการไหวสะเทือนบริเวณหมู่เกาะฟิลิปปินส์และพื้นที่ใกล้เคียง - ณัฐพล ธนาวุฒิ (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
This study aims mainly to analyze the seismicity rate change for detecting seismic quiescence in the Philippines islands and the adjacent areas by using earthquake catalogues from the National Earthquake Information (NEIC), the International Seismological Center (ISC) and the Global CMT Catalogue (GCMT). The study area was covered Latitude of 4.10S -26.10N and Longitude of 109.99 -132.22E. After improving the earthquake catalogue process, we chose earthquake events that possibly refer to seismotectonic setting to represent our case study for 34 events (MW>7.0). Then, prove retrospective tests with reasonable conditions, N = 25 events and TW= 2.0 years. After the retrospective test, we were found three quiescence-anomaleous areas, might be risk for the upcoming moderate-to-large earthquakes in present day map consist of eastern of Bandar Seri Begawan, eastern of Manila and western Davao.